Relationships among training stress, mood and dehydroepiandrosterone sulphate/cortisol ratio in female cyclists - Bouget, M.; Rouveix, M.; Michaux, O.; Pequignot, J.-M.; Filaire, E. (Journal of Sports Sciences, 2006)
In this study, we examined the effect of rapidly increased training volume and intensity on hormonal responses (salivary cortisol [C] and urinary dehydroepiandrosterone sulphate [DHEA-S]) and recovery-stress state perceived by 12 female cyclists. Over the 4-day experimental period, there was an average increase in training load of approximately 122% compared with that during the previous 12 days. Scores on subscales of the Recovery Stress Questionnaire for Athletes increased for the somatic component of stress (Fatigue, Emotional Stress and Social Stress; P < 0.05) and decreased the factor indicating recovery (General Well Being; P < 0.05) after the heavy training period. The training programme increased resting concentrations of salivary cortisol (P < 0.05) and decreased the DHEA-S/C ratio (P < 0.05). The increase in training load of cyclists was correlated with this hormonal ratio (r = -0.48, P < 0.05). Changes in resting cortisol concentration as a result of heavy training stress were positively related to the change in Physical Complaints (r = 0.69, P < 0.01). Negative relationships were also found between changes in the DHEA-S/C ratio and changes in the somatic component of stress. The present results suggest that there is a dose-response relationship between increased training load, resting DHEA-S/C ratio and subjective assessment of stress and recovery, implying that this ratio could be used as an indicator of training status in female athletes.